Analisa Kebutuhan Pengembangan Bahan Ajar Berdiferensiasi Pendidikan Seksual Bagi Mahasiswa - Rofiah, Siti; Jasminto; Mahsun, Ali; Kibtiyah, Asriana; Mohamad Nur Salim; Supratno, Haris (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2025)
Sexual education is a crucial aspect in shaping the character and awareness of university students regarding ethics and moral responsibility in personal and social life. However, the implementation of sexual education in higher education institutions often failas to meet the diverse needs of students, who come from different backgrounds, levels of understanding, and learning needs. Thus tudy aims to anakyze the need for differentiated instructional materials in sexual education for university students, focusing on differentiation in terms of learning readiness, interests, learning styles, levels of understanding. The research method used is a needs survey involving 46 students from the PGMI study programs, using a questionnaire to collect data. The results show that although most students have previously studied the material, their understanding remains at varying level – some high, some moderate, and most low. On the other hand, the majority of students expressed a high level of interest in sexual education from an Islamic prespective, yet demonstrated diverse preferences in strategies, media, and types of learning tasks. These findings highlight the importance of developing instructional materials that can accommodate students diverse characteristic through a differentiated approach, in term of content, procces, and product. Thus, the development of differentiated instructional materials will not only enhance the effectiveness of learning, but also encourage active student engagement and strengtrhen their understanding of Islamic values related to sexual issues in a reflective, responsible, and applicable manner.